Respon Komunitas Bacillariophyceae terhadap Kualitas Air Sub-Das Kedurang: Bukti Dominansi Synedra ulna dalam Kawasan RHL - Meliya Wati; Putri Lisya Anggraini; Novia Duya (Universitas PGRI Silampari, 2025)
This study aims to examine the dominance of Synedra ulna as a bioindicator in assessing the water quality of the Kedurang Sub-watershed (Sub-DAS) located within the Forest and Land Rehabilitation (RHL) area of Batu Ampar Village, South Bengkulu. A quantitative and qualitative approach was used by measuring physicochemical parameters (temperature, pH, TDS, and DO) and analyzing the phytoplankton community structure, with a focus on the Bacillariophyceae class. Samples were collected purposively from two stations with different ecological conditions. The results showed that Synedra ulna was highly dominant, with dominance index values of 0.75 and 0.92 at Stations 1 and 2, respectively. The water's physicochemical conditions were within the optimal range for phytoplankton growth, with temperatures of 24.9–29.8°C, pH of 7.5–8.0, TDS of 103–125 ppm, and DO of 7.9–8.2 ppm. The high dominance of S. ulna indicates moderate ecological pressure due to anthropogenic activities and suggests that the aquatic ecosystem is in a recovery phase. These findings highlight the potential of Synedra ulna as an effective ecological indicator for monitoring the success of forest and land rehabilitation efforts